OESTRUS MONITORING CHART’: A TOOL TO IMPROVE POST BREEDING OESTRUS OBSERVATION IN A DAIRY FARM - S. Satheshkumar; S. Ganesh Kumar; S. Senthilkumar; A. Ganesan; M. Murugan; M. Thirunavukkarasu; J. Johnson Rajeswar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Oestrus detection plays an important role in the reproductive management of a dairy farm. To improve the post-breeding oestrus observation practice among the farmers, a reproductive management tool called ‘Oestrus Monitoring Chart’ (OMC) was designed and developed. The effectiveness of this technology on oestrus detection, timed artificial insemination and pregnancy diagnosis was studied in a small scale crossbred cattle dairy farm. Breeding parameters viz., number of inseminations carried out per animal, duration between two successive inseminations for each animal, duration between artificial insemination and pregnancy check-up and conception rate was studied for a period of one year before (G1) and one year after installation of OMC (G2). Perusal of the data revealed that the duration between successive artificial insemination (AI) and the duration between AI and pregnancy diagnosis was significantly (P < 0.01) decreased in G2 group when compared with G1 group. The conception rate was also significantly improved after the installation of the OMC and introduction of OMC as a reproductive management tool improved the oestrus detection attitude among the farm personnel.